1985
DOI: 10.1002/ana.410180102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular regulation and lesions of the central nervous system

Abstract: The central nervous system has an important role in the second-to-second regulation of cardiac activity and vasomotor tone. Central lesions that lead to a disturbance in autonomic activity tend to cause electrocardiographic and pathological evidence of myocardial damage, cardiac arrhythmias, and disturbances of arterial blood pressure regulation. To a great extent such cardiovascular disturbances result from alterations in sympathetic activity. Similar alterations in sympathetic activity can occur under condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(69 citation statements)
references
References 136 publications
2
67
0
Order By: Relevance
“…6,7 We also confirmed previous reports 12,27 that systolic and diastolic blood pressure is lower in individuals with manifest Alzheimer's disease and vascular dementia than in nondemented individuals and that blood pressure decreases with dementia severity. These findings are supported by reports that blood pressure declines in the years preceding dementia onset 11 and further declines during the course of Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6,7 We also confirmed previous reports 12,27 that systolic and diastolic blood pressure is lower in individuals with manifest Alzheimer's disease and vascular dementia than in nondemented individuals and that blood pressure decreases with dementia severity. These findings are supported by reports that blood pressure declines in the years preceding dementia onset 11 and further declines during the course of Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 90%
“…With increasing age, the prevalence of cerebral disorders such as Alzheimer's disease and vascular dementia increases, 4 but cerebral changes also occur in normal aging. 5 Several brain areas suggested to have a role in blood pressure regulation [6][7][8] are affected in Alzheimer's disease 9 and in normal aging. 5 Brain disorders may thus also contribute to the decrease in blood pressure observed in the very elderly.…”
mentioning
confidence: 99%
“…12 Cardiac complications of acute stroke are common, may be associated with adverse prognosis, and include arrhythmias and symptoms related to concomitant ischemic heart disease. 13,14 As in acute myocardial infarction patients, impaired BRS may be important in the development of such complications. We have previously shown that increased beat-tobeat BP variability, perhaps reflecting impaired cardiac BRS, is associated with 30-day outcome; the odds ratio for a poor outcome was 1.32 (range, 1.1 to 1.7) for every 1 mm Hgincrease in mean arterial BP variability.…”
mentioning
confidence: 99%
“…BP control is supported by a descending sympathoexcitatory pathway from the rostral ventrolateral medulla to the intermediolateral cell column in the spinal cord, and damage to these areas can cause severe hypotension (1,3). Based on studies of anesthetized animals, the rostral ventrolateral medulla seems to play major roles in BP regulation (4).…”
Section: Discussionmentioning
confidence: 99%
“…A brain lesion can potentially produce arterial hypotension, as well as hypertension (1). Because the medulla oblongata contains vasomotor centers that control peripheral vascular tone and blood pressure (BP), damage to the medulla oblongata due to ischemia, tumor, demyelination, extrinsic compression, and other causes may produce a failure of cardiovascular regulation, including paroxysmal neurogenic hypertension (2).…”
Section: Introductionmentioning
confidence: 99%